The VALTIVE1 study protocol: a study for the validation of Tie2 as the first tumour vascular response biomarker for VEGF inhibitors - Margherita Carucci; Andrew Clamp; Cong Zhou; Chris Hurt; Rosalind Glasspool; Phillip J. Monaghan; Sally Thirkettle; Michael Wheatley; Madia Mahmood; Monica Narasimham; Tracy Cox; Hilary Morrison; et al. (BMC Cancer)
Abstract Background Anti-angiogenic, VEGF inhibitors (VEGFi) increase progression-free survival (PFS) and, in some cases, overall survival in many solid tumours. However, their use has been compromised by a lack of informative biomarkers. We have shown that plasma Tie2 is the first tumour vascular response biomarker for VEGFi in ovarian, colorectal and gall bladder cancer: If plasma Tie2 concentrations do not change after 9 weeks of treatment with a VEGFi, the patient does not benefit, whereas a confirmed reduction of at least 10% plasma Tie2 defines a vascular response with a hazard ratio (HR) for PFS of 0.56. The aim of the VALTIVE1 study is to validate the utility of plasma Tie2 as a vascular response biomarker and to optimise the Tie2-definition of vascular response so that the subsequent randomised discontinuation VALTIVE2 study can be powered optimally. Methods VALTIVE1 is a multi-centre, single arm, non-interventional biomarker study, with a sample size of 205 participants (176 bevacizumab-treated participants + 29 participants receiving bevacizumab and olaparib/PARPi), who are 16 years or older, have FIGO stage IIIc/IV ovarian cancer on treatment with first-line platinum-based chemotherapy and bevacizumab. Their blood plasma samples will be collected before, during, and after treatment and the concentration of Tie2 will be determined. The primary objective is to define the PFS difference between Tie2-defined vascular responders and Tie2-defined vascular non-responders in patients receiving bevacizumab for high-risk Ovarian Cancer. Secondary objectives include defining the relationship between Tie2-defined vascular progression and disease progression assessed according to RECIST 1.1 criteria and assessing the impact of PARPi on the plasma concentration of Tie2 and, therefore, the decision-making utility of Tie2 as a vascular response biomarker for bevacizumab during combined bevacizumab-PARPi maintenance. Discussion There is an urgent need to establish a test that tells patients and their doctors when VEGFi are working and when they stop working. The data generated from this study will be used to design a second trial aiming to prove conclusively the value of the Tie2 test. Trial registration ClinicalTrials.gov identifier: NCT04523116. Registered on 21 Aug 2020.